2003
DOI: 10.1161/01.cir.0000095788.78169.af
|View full text |Cite
|
Sign up to set email alerts
|

Infarct Remodeling After Intracoronary Progenitor Cell Treatment in Patients With Acute Myocardial Infarction (TOPCARE-AMI)

Abstract: Background-Experimental and initial clinical studies suggest that transplantation of circulating blood-(CPC) or bone marrow-derived (BMC) progenitor cells may beneficially affect postinfarction remodeling processes after acute myocardial infarction (AMI). To relate functional characteristics of the infused cells to quantitative measures of outcome at 4-month follow-up, we performed serial contrast-enhanced MRI and assessed the migratory capacity of the transplanted progenitor cells immediately before intracoro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
108
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 500 publications
(114 citation statements)
references
References 38 publications
(40 reference statements)
5
108
1
Order By: Relevance
“…Moreover, the demonstration that GFs induce translocation of resident progenitor cells to the infarct, rebuilding the lost myocardium in larger mammals, closes the gap between rodents and humans and strengthens the feasibility and applicability of local stem cell activation in the patient population. This strategy is minimally invasive and avoids the complication of rejection and the effects of time on the onset of therapy linked to the acquisition and in vitro expansion of the patient's own progenitor cells (24,25). Additionally, the risks inherent in the systemic mobilization of a large number of hematopoietic and other stem cells to nontarget organs are prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, the demonstration that GFs induce translocation of resident progenitor cells to the infarct, rebuilding the lost myocardium in larger mammals, closes the gap between rodents and humans and strengthens the feasibility and applicability of local stem cell activation in the patient population. This strategy is minimally invasive and avoids the complication of rejection and the effects of time on the onset of therapy linked to the acquisition and in vitro expansion of the patient's own progenitor cells (24,25). Additionally, the risks inherent in the systemic mobilization of a large number of hematopoietic and other stem cells to nontarget organs are prevented.…”
Section: Discussionmentioning
confidence: 99%
“…Several cell types have been used in an effort to reconstitute dead myocardium. Among them, endothelial progenitor cells and bone marrow-derived cells have been the most successful (2)(3)(4)(5)(6). However, preliminary long-term studies with bone marrow-derived cells indicate that the new myocytes do not acquire the adult phenotype but resemble neonatal cells, which die with time by apoptosis (P.A., unpublished data).…”
mentioning
confidence: 99%
“…[39][40][41] We used Lymphoprep for BMMNC isolation and included heparin in our isolation protocol, which is similar to previous studies that showed potential clinical effects. 13,38,42 Heparin has been reported to negatively affect cellular homing by impairment of the SDF-1α/CXCR4 axis. 40 We cannot exclude that the use of heparin in our isolation procedure could have reduced the potency of our product.…”
Section: Discussionmentioning
confidence: 99%